Newly Qualified General Nurses' Experiences of Internship: A Republic of Ireland Cross-Sectional Study - Mooney, Mary (university College Dublin, 2023)
Background/ Aim Pre-registration nursing education varies across the globe. The uniqueness of the Irish degree in general nursing is the inclusion of a 36-week internship placement. The aim of internship is to consolidate theoretical learning and support the achievement of clinical competence. Some countries include internship as part of the transition phase, but Ireland includes internship as part of the undergraduate degree. The aim of this study was to ascertain Newly Qualified General Nurses’ (NQGNs) experiences of internship and identify the value of it in preparing them for transition to the role of registered nurse. Method The phase one findings of a sequential explanatory mixed methods study are presented. Data were collected using Experience of Internship Questionnaire. Ethical approval was obtained from the Research Ethics Committee, Trinity College Dublin. Results In total, 193 NQGNs completed the questionnaire. Most respondents (92.8%, n=128) agreed or strongly agreed that internship consolidated their learning and helped them to link theory to practice. Just over two thirds of respondents (69.6%, n=96) were satisfied with the opportunities made available to them to advance the knowledge and skills required for registration. The respondents were provided with an opportunity to explain reasons for dissatisfaction. The main reasons provided were staff shortages, which hampered their learning (n=16), particularly in relation to accompanying nurses on medication rounds and preparing intravenous medications under supervision. Some respondents reported dissatisfaction with a lack of opportunity to practice necessary clinical skills (n=5). Conclusion The results from phase one showed a good level of satisfaction with internship and opportunities to link theory to practice. However, areas for improvement such as opportunities in medication management under direct supervision and other key skills were also identified. The impact of staff shortages on student learning during internship were highlighted particularly in relation to gaining experience in key skills.
Book of abstracts international research conference.
UCD SNMHS (2023) Inaugural International Research Conference: Scanning Horizons, Driving Change, Building a Healthier World. Dublin UCD SNMHS.
Keywords: NURSING EDUCATION; Nursing; Undergraduate Education